Tajiks of jizzakh oasis: traditional way of life, customs and traditions and rituals - DAVLATOVA, KHAKIMA; NEMATOV, OZODBEK (The journal of contemporary issues in business and government, 2021)
This article discusses the traditional lifestyle of the Tajiks of the Jizzakh oasis, and their customs and traditions and rituals. The article also provides examples of customs and traditions and rituals of the Tajiks in the Jizzakh oasis, as well as brief information about their lifestyle and rituals. It is no coincidence that the first president of the Republic of Uzbekistan said, “Uzbeks and Tajiks are the only bilingual people,” because the customs of the Uzbek and Tajik peoples have always been similar to each other, whether it is wedding ceremonies or the culture of dress.